Psychopathic traits in a representative sample of Finnish male prisoners. (February 2014) - Jüriloo, Alo; Lauerma, Hannu; Holmalahti, Tuomo; Tyni, Sasu; Aarnio, Jorma; Viitanen, Päivi; Wuolijoki, Terhi; Mattila, Aino; Lintonen, Tomi; Joukamaa, Matti; Vartiainen, Heikki
Abstract: Background: The psychopathic traits measured with the Hare Psychopathy Checklist-Revised (PCL-R) in a representative national prisoner sample have not been studied in Finland before. It has been unclear whether there could occur some national differences or whether the PCL-R can be used for assessing psychopathic traits in the Finnish forensic settings. Aims: Our aim was to study the distribution of psychopathic traits in the Finnish male prisoners as well as the correlations of these traits with DSM-IV disorders and to compare the sample with similar samples of Europe and America. Methods: 171 male prisoners representing all Finnish sentenced male offenders (about 3300) were studied using the PCL-R, SCID-I and SCID-II. Results: The results of the first Finnish study utilizing the PCL-R in a representative national sample of male prisoners were quite similar to the findings of the previous studies of male prisoners carried out in North America, the UK and Sweden. The scores of the interpersonal facet are lower in this sample than in the sample of North America. In total, 16.4% of the Finnish male prisoners can be diagnosed as having a psychopathic disorder. Conclusions: The PCL-R is a reliable and valid measure of the psychopathy construct of the Finnish male prisoners. The PCL-R is applicable to the Finnish offenders and it is a useful tool for assessing psychopathy in the Finnish criminal justice settings.